THE USE OF 20-SQUARES: ADD ONE MORE WORD AND WORD CLAP GAMES TO TEACH VOCABULARY - Putri, Afrilita Mardiana; Sutopo, Djoko; Bharati, Dwi Anggani Linggar (ELT Forum: Journal of English Language Teaching, 2017)
The study has objectives to find out whether 20-Squares: Add One More Word can be used in teaching vocabulary to the seventh graders of SMPN 5 Magelang and to find out whether there is a significant difference of the use of 20-Squares: Add One More Word and Word Clap Games in the studentsâ vocabulary achievement. The subjects of this study are two classes of seventh grade of SMPN 5 Magelang. One class serves as the control group and one class as the experimental group. This is a quasi-experimental research by using non-equivalent control group design. The instrument used is tests. The result shows that 20-Squares: Add One More Word improves the studentsâ vocabulary mastery. The result of t-test analysis shows that the experimental group get better achievement than the control group. In the pre-test, the average score of the experimental group is 63 and the control group is 62.67. In the post-test, the  average  score  of  experimental  group  is  81,17  and  the  control  group  is 70,67. The result of the t-test is 3.895 and t-table is 1.67. It means that the t-value is higher than t-table (3.895 > 1.67). Therefore, it can be concluded that 20-Squares: Add One More Word can be used as an alternative way in teaching vocabulary.